Contribution of Ecotourism Implementation to Environmental Sustainability Waterfall Nature Tourism in Banjar Bhuana Sari, Wanagiri Village - I Putu Ananda Citra; Ida Bagus Arya Yoga Bharata; Restu Ade Yanti; Lutfiatul Janah (Politeknik Negeri Bali, 2025)
The concept of ecotourism presents a suitable approach to tourism management in Bali, given its abundant natural attractions. One such attraction is the Banjar Bhuana Sari Waterfall in Wanagiri Village, Sukasada District, Buleleng Regency, Bali Province. This study aims to identify and analyze the potential of this natural site for ecotourism development by examining three key aspects: (1) the tourism potential of the site, (2) the level of community participation, and (3) the contribution of tourism to the local area. Data was collected through observation, interviews, questionnaires, and literature review. The data were then analyzed using a rating or scoring system to classify each indicator. The findings reveal that Banjar Bhuana Sari Waterfall possesses substantial potential for ecotourism development. High levels of community participation play a significant role in maintaining the site’s sustainability. However, while the natural environment is generally well-preserved, further improvement is needed regarding tourism facilities and infrastructure. Additionally, the economic and social contributions of tourism to the local community, although present, require enhancement to ensure a more impactful and sustainable tourism model. Overall, the research highlights the importance of strengthening both environmental management and tourism benefits to support the long-term development of ecotourism at Banjar Bhuana Sari Waterfall.